PEMUNGUTAN PAJAK AMERIKA PADA YOUTUBER INDONESIA BERDASARKAN PERATURAN U.S. INTERNAL REVENUE CODE CHAPTER 3 - Khasanah, Nurul Lailia; Herawati, Nurul (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
The purpose of this study is to examine the implementation of income tax collection for Youtubers based on U.S. Regulations – Internal Revenue Code Chapter 3, explores the compliance of Indonesian Youtubers to pay taxes under U.S. Regulations, and reviews the readiness of Youtubers to pay income tax that applies in Indonesia with regulations that are almost the same as U.S. regulations. A qualitative method with a descriptive approach is used in this study. There were two Youtubers as informants. Youtuber informants are those who have become Youtube Program Partners (YPP) and have received American tax deductions. The results are that Google is obliged to collect tax data from all Youtubers who are outside the United States, regardless of whether Youtubers earn income from United States viewers or not. Tax deductions are done automatically, making Youtubers unable to avoid tax deductions given by America. In contrast to the tax deductions made by the American Government, some Indonesian Youtubers still do not understand or know the income tax that applies in Indonesia. In addition, several other Youtubers take advantage of the imperfect tax regulations in Indonesia, to commit tax evasion consciously.